The seed water content as a time-independent physiological trait during germination in wild tree species such as Ceiba aesculifolia - Gómez-Maqueo, Ximena (Sci Rep, 2020)
Seeds constitute a key physiological stage in plants life cycle. During seed germination, there is a spatial-temporal imbibition pattern that correlates with described physiological processes. However, only the moment of testa rupture has been described as a critical, discrete stage. Could a specific relative water content (RWC) value reflect a physiological stage useful for comparisons between seed batches? We tracked seed-by-seed imbibition during germination to homogenize sampling and selected a transcriptomic approach to analyse the physiological transitions that occur in seed batches collected in different years and with contrasting phenotypic responses to a priming treatment. The seed RWC reflected the transcriptional transitions that occur during germination, regardless of imbibition time or collection year, and revealed a set of biological processes that occur in the dry seed and during early germination are associated with the phenotypic response to priming. As climate shifts, so do the timing of developmental events important for determining organismal fitness, and poses another challenge to the comprehension of molecular and physiological processes driving the interaction between organisms and environment. In this study, we demonstrate that the use of physiological traits, specific to a particular developmental stage, is a reliable time-independent approach.